Kandungan Lignoselulosa Hasil Fermentasi Limbah Serbuk Gergaji Kayu Dan Jerami Padi Menggunakan Inokulum Kotoran Kambing Dengan Variasi Lama Inkubasi - Susilowati, Dwi; , Triastuti Rahayu, S.Si, M.Si (2016)
Waste sawdust and rice straw is one berlignoselulosa materials that can be parsed into lignin, cellulose, and hemicellulose. Inoculum goat droppings contain bacteria capable lignolitik cellulolytic and remodel cellulose and lignin. The purpose of this study was to determine the levels of lignocellulose fermented sawdust wood waste and rice straw using inoculum goat manure with a variety of long incubation. The method used is the experimental method completely randomized design (CRD) two factors, namely the first substrate lignocellulosic (sawdust (L1) and rice straw (L2)) and factor II long incubation (control (I1), 20 days (I2) and 30 days (I3)) with 2 replications. Lignocellulosic substrates inoculation using goat droppings subs were then incubated for 20 days and 30 days. After incubation measured the content of lignin, cellulose and hemicellulose using Chesson-Datta. Data were analyzed with descriptive quantitative. The results obtained by the content of lignocellulosic waste wood sawdust mixture with inoculum fermented goat manure was better than the waste rice straw. The best treatment in L1I3, the highest cellulose content to 34% from 16% (control), while the lowest lignin content in treatment L1I3 that 7% from 25% (control).